Andragogy Model to Improve Digital Technology Competence of High School Teachers - Jakaria, Jakaria; Permana, Elih Sudia; Saripah, Iip; Saepudin, Asep; Yahya, Faridah Hanim (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to develop a competency-based andragogy training model to improve the digital technology competence of teachers at the Cianjur Regency Mover School. In the digital era, teachers' digital competence is very important, but initial observations show that many teachers still have difficulty in mastering learning technology. The competency-based training model with an andragogy approach is considered effective because it is tailored to the needs and experiences of adult participants. This study uses a qualitative approach with a systematic ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. Data collection was carried out through observation, interviews, questionnaires, and documentation studies. The results of the study showed that most teachers were aware of the importance of digital technology, but needed further support in mastering digital learning applications and media. The development of a competency-based training model is expected to accelerate digital transformation in education. This study provides theoretical and practical contributions to the development of competency-based and andragogy teacher training policies in the digital era.